Analysis of the correlation between the serum residual cholesterol level at admission and the risk of death after discharge in patients with ischemic stroke: Serum residual cholesterol level in ischemic stroke - Xu, De; Duan, Ruijuan; Zhu, Ruiqi; Huang, Yinghua; Chen, Shiyu (Journal of Medical Biochemistry, 2025)
[Objective] To investigate the relationship between residual cholesterol (RC) levels at admission and the risk of death after discharge in patients with ischemic stroke (IS). [Methods] A total of 2021 IS patients aged 35-80 years were selected as the study objects, and death endpoint data after discharge were collected. Restricted cubic spline (RCS) regression was used to analyze the dose‒response relationship between the RC at admission and the risk of death. The hazard ratio (HR) and 95% CI were calculated via Cox regression to analyze the association between the RC level at admission and the risk of death after discharge in patients with IS. [Results] According to the RCS model, RC levels were nonlinearly associated with deaths from IS and other causes (P<0.001). With the median RC level as the cutoff value, the subjects were divided into a low RC group (RC<0.72 mmol/L) and a high RC group (RC≥0.72 mmol/L). Compared with those in the high RC group, the age and male ratio in the low RC group were significantly greater. The fasting blood glucose (GLU), total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), non-high-density lipoprotein cholesterol (HDL-C), apolipoprotein A-1 (ApoA-1), and apolipoprotein B (ApoB) levels and TG/HDL-C, TG/HDL-C, LDL-C/HDL-C and diabetes rates were significantly lower (P<0.05 0.01). Cox regression analysis revealed that without adjusting for covariates, the high-level RC group presented a lower risk of all-cause death than did the low-level RC group did (HR = 0.765, 95% CI: 0.619 0.946, P = 0.013) and a lower risk of death from IS (HR = 0.638, 95% CI: 0.435 0.936, P = 0.022). After adjusting for sex, age, smoking, drinking, hypertension, and diabetes, the high-level group still had a lower risk of all-cause death (HR = 760, 95% CI: 0.614 0.941, P = 0.012) and a lower risk of death from IS (HR = 0.653, 95% CI: 0.444-0.961, P = 0.031). Male sex (HR = 0.753, 95% CI: 0.572 0.990, P = 0.042), age ≥65 years (HR = 0.75, 95% CI: 0.594 0.959, P = 0.021), nonsmoking (HR = 0.746, 95% CI: 0.590 0.943, P = 0.014), not drinking (HR = 0.735, 95% CI: 0.588 0.919, P = 0.007), hypertension (HR = 0.738, 95% CI: 0.580 0.940, P = 0.014), and not having diabetes (HR = 0.724, 95% CI: 0.561 0.934, P = 0.013) were associated with a statistically significant reduction in the risk of all-cause death. Age ≥65 years (HR = 0.598, 95% CI: 0.391 0.916, P = 0.018), nonsmoking status (HR = 0.628, 95% CI: 0.408 0.967, P = 0.035), nonalcoholic status (HR = 0.656, 95% CI: 0.439-0.979, P = 0.039), not complicated with hypertension (HR = 0.321, 95% CI: 0.108 0.957, P = 0.041) and no diabetes mellitus (HR = 0.607, 95% CI: 0.389 0.947, P = 0.028), and RC≥ 0.72 mmol/L were associated with a statistically significant reduction in the risk of death from IS. After adjusting for age, sex, smoking history, drinking history, hypertension history, and diabetes history, there was no significant association between RC≥ 0.72 mmol/L and the risk of all-cause death in males, those aged ≥65 years, or nondiabetic patients (P > 0.05 for all). There was no significant association between RC≥ 0.72 mmol/L and an increased risk of death from IS in patients aged ≥65 years, nonsmokers, nondrinkers, nonhypertensive patients, or nondiabetic patients (P > 0.05 for all). Compared with those in the high RC group, the IS patients in the low RC group had a lower incidence of all-cause death, IS death and other causes of death and a higher survival rate. [Conclusion] An RC < 0.72 mmol/L at admission is associated with an increased risk of all-cause death and long-term IS death after discharge.